Acetamido-TEMPO mediated electrochemical oxidation of alcohols to aldehydes and ketones - Schroeder, Chelsea M. (2023)
A protocol for the oxidation of alcohols to aldehydes and ketones employing an electrochemical aminoxyl-mediated reaction is presented. The approach employs a catalytic amount of the radical and the use of a base is not required. It is performed using readily available electrodes in a commercially available electrochemistry apparatus and does not require a reference electrode. The methodology is applicable to a range of structurally and electronically diverse substrates, including the oxidation of primary alcohols to aldehydes rather than the more commonly formed carboxylic acids.